Search for T and CP violation in B0-B-0 mixing with inclusive dilepton events. - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; Chen, G; et al. (2002)
We report the results of a search for T and CP violation in B0-B-0 mixing using an inclusive dilepton sample collected by the BABAR experiment at the PEP-II B Factory. The asymmetry between l+l+ and l-l- events allows us to compare the probabilities for B-0-->B0 and B0-->B-0 oscillations and thus probe T and CP invariance. Using a sample of 23 x 10(6) BB- pairs, we measure a same-sign dilepton asymmetry of A(T/CP) = [0.5+/-1.2(stat)+/-1.4(syst)]%. For the modulus of the ratio of complex mixing parameters p and q, we obtain q/p = 0.998+/-0.006(stat)+/-0.007(syst).